Corrigendum to "A long note on Mulders' short product" [J. Symb. Comput. 37 (3) (2004) 391–401]. (January 2015) - Hanrot, G.; Zimmermann, P.
Abstract: We correct a minor mistake in the paper ofHanrot and Zimmermann (2004) .